KAPITALISASI PENDIDIKAN: SYSTEMATIC LITERATURE REVIEW - Syamsul Arifin; Fahmi Ashari S Sihaloho (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2023)
This study presents a systematic review of the literature discussing the capitalization of education, which refers to the phenomenon where economic and market values increasingly dominate the education sector. The Systematic Literature Review (SLR) method was used to identify, analyze, and synthesize the latest findings from various relevant literature sources. The results of this review reveal various trends, impacts, and challenges faced by education in a global context increasingly influenced by economic dynamics. Additionally, this study explores how the capitalization of education affects educational policies, teaching practices, and the accessibility of education for various societal groups. By gaining a deeper understanding of these aspects, this research provides valuable insights for designing more equitable and sustainable educational strategies that can accommodate economic needs without sacrificing the principles of inclusivity and fairness in education. These findings are expected to serve as a foundation for more informed decision-making in developing future education systems.